Two new species of the genus Brithura Edwards from China, with a key to world species (Diptera, Tipulidae) - Liu, Qifei; Yang, Ding (Zootaxa, 2009)
The following two new species of the genus Brithura Edwards from China are described: B. jinpingensis sp. nov. and B. guangxiensis sp. nov. A key to the world species of the genus Brithura is presented.